2015
DOI: 10.1177/0146167215569493
|View full text |Cite
|
Sign up to set email alerts
|

Threats to Social Identity Can Trigger Social Deviance

Abstract: We hypothesized that threats to people's social (i.e., group) identity can trigger deviant attitudes and behaviors. A correlational study and five experiments showed that experiencing or recalling situations associated with the devaluation of a social identity caused participants to endorse or engage in deviant actions, including stealing, cheating, and lying. The effect was driven by the tendency to construe social identity threats not as isolated incidents but as symbolic of the continuing devaluation and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…First, our findings join a growing body of research that explores why class-based hierarchies persist. Whereas past work has highlighted how class-based hierarchies perpetuate because of explicit discrimination and prejudice of decision makers (Belmi et al, 2015;Bird & Bogart, 2001;Darley & Gross, 1983;Kang et al, 2016;Kraus & Keltner, 2013;Laudicella et al, 2012;Laurin et al, 2011;Rivera, 2016;Stephens et al, 2012), our work highlights how inequality may inadvertently arise even in the absence of explicit discrimination or prejudice (e.g., DiTomaso, 2013). Here, we test the idea that class-based inequalities may be perpetuated because high-class contexts imbue individuals with overly positive perceptions of themselves that make them appear more competent in the eyes of observers.…”
Section: Overview Of Researchmentioning
confidence: 72%
“…First, our findings join a growing body of research that explores why class-based hierarchies persist. Whereas past work has highlighted how class-based hierarchies perpetuate because of explicit discrimination and prejudice of decision makers (Belmi et al, 2015;Bird & Bogart, 2001;Darley & Gross, 1983;Kang et al, 2016;Kraus & Keltner, 2013;Laudicella et al, 2012;Laurin et al, 2011;Rivera, 2016;Stephens et al, 2012), our work highlights how inequality may inadvertently arise even in the absence of explicit discrimination or prejudice (e.g., DiTomaso, 2013). Here, we test the idea that class-based inequalities may be perpetuated because high-class contexts imbue individuals with overly positive perceptions of themselves that make them appear more competent in the eyes of observers.…”
Section: Overview Of Researchmentioning
confidence: 72%
“…Belmi, Barragan, Margaret, and Cohen () suggested that situations involving a social identity threat easily generalizes to a global sense that one's group is maltreated in society, which in turn leads to antisocial attitudes, intentions, and disruptive behaviors. Our argument here is similar, but we extend it by noting that perceived mistreatment of one's group not only influences understandings of how a particular society works (in this case Danish society), but also how the world as a whole works.…”
Section: Studymentioning
confidence: 99%
“…GD may also intersect with other social oppressions and discriminations, such as socio-economic inequalities and relative deprivations, and ethnic and racial discriminations (e.g., Denton, & Walters, 1999), which amplify its effects yielding linear and non-linear cumulative dynamics (Kira, Alawneh, Aboumediene, Lewandowski, & Laddis, 2014). There is experimental evidence that threats to social identity can trigger social deviance, which was driven by the tendency to construe social identity threats not as isolated incidents but as symbolic of the continuing devaluation and disrespectful treatment of one's group (e.g., Belmi, Barragan, Neale, & Cohen, 2015). Gender discrimination, subtle and blatant, is based, in such structures, on man's assumed/perceived superiority, control, and dominance over woman's identity on familial, social, political, religious and can spillover to eating, decision-making and attention (Inzlicht & Kang, 2010).…”
Section: A Traumatology/oppression Conceptual Model Of Gdmentioning
confidence: 99%
“…Gender discrimination, subtle and blatant, is based, in such structures, on man's assumed/perceived superiority, control, and dominance over woman's identity on familial, social, political, religious and can spillover to eating, decision-making and attention (Inzlicht & Kang, 2010). They can also lead to social deviance (Belmi, Barragan, Neale, & Cohen, 2015). People, when they feel devalued, tend to act impulsively (Gino et al, 2011) and anti-socially (Gibbons et al, 2012;Kamans, Gordijn, Oldenhuis, & Otten, 2009).…”
Section: A Traumatology/oppression Conceptual Model Of Gdmentioning
confidence: 99%